Augmentation of Psychotherapy through Alternative Preconscious Priming: A Case Series Exploring Effects on Residual Symptoms - Zidani, Melha; Audet, Jean-Sébastien; Borgeat, François; Aardema, Frederick; O’Connor, Kieron Philip; Khazaal, Yasser (Frontiers in Psychiatry, 2017)
The current paper describes a case series using a new strategy for facilitating change based on Augmentation of Psychotherapy through Alternative Preconscious Priming (APAP) (Borgeat et al., 2013) in the treatment of eight treatment resistant patients suffering from social phobia or generalized anxiety disorder. The patients had previously only shown a partial response to CBT despite good treatment adherence. The patients completed APAP using a computerized program, which consisted of three steps during which alternative, more functional thoughts and beliefs relevant to the idiosyncratic difficulties experienced by the patients were formulated. Subsequently, these formulations were recorded and mixed with masking relaxing music, which the patient listened in a passive state twice daily for 20 minutes for a period of 8 weeks. This case series aimed to assess the effect and acceptability of APAP using quantitative and qualitative measures administered before, after and 16 weeks’ post-treatment. Results showed a reduction in dysfunctional idiosyncratic thoughts reported by most patients, as well as mild improvements in anxiety and important improvements in quality of life. APAP could be a valuable addition to CBT by facilitating or enhancing cognitive and symptom change. Further studies are needed to confirm these promising results.